Investigating the Challenges Facing Mentally Retarded Adolescents in Acquiring Self-Empowerment Skills - Ataeikachoei, Mitra; Falsafinejad, Mohamadreza; Khodabakhshi koolaee, Anahita (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: Disability is a global phenomenon that has been discussed in all societies throughout history, so that 10% of the world's population is physically, mentally, psychologically, and socially disabled according to the World Health Organization (WHO). So, officials and macro-policymakers in the field of the disabled should provide appropriate conditions to promote the mental health of families with children with special disabilities by taking the necessary measures. Accordingly, this study was conducted to identify the challenges facing mentally retarded adolescents in acquiring self-empowerment skills. Methods: This is a qualitative study based on the nature of the data and a baseline study in terms of the type of theory. The statistical population included specialists and practitioners working in centers for the education and care of mentally retarded adolescents, mothers, and caregivers who were selected by purposive sampling in Tehran in 2019. Data were collected through semi-structured 35- to 45-minute interviews to reach saturation with 15 specialists and 10 mothers and caregivers. Data were analyzed by the method developed by Strauss and Corbin. Results: According to the results, the challenges in acquiring self-empowerment skills in mentally retarded adolescents could be classified as parental ignorance, rejection, economic, social, and family constraints, abuse/harassment, feelings of inadequacy, inefficiency, Inadequate professional and welfare support, social inequality, lack of enforcement of laws, lack of jobs concerning disability, educational malfunctions, and lack of qualified trainers. Conclusion: The results showed that a lack of awareness of the abilities and potentials of mentally retarded adolescents in acquiring self-empowerment skills creates challenges for them to achieve this goal. So, special attention should be paid to mentally retarded adolescents and careful consideration of the challenges they face in acquiring self-improvement skills. This can lead to solutions to increase their social skills, life skills, and self-empowerment.